WAKAF UANG DAN PERANNYA DALAM PENGUATAN KETAHANAN KELUARGA MUSLIM - Djati PS, Syailendra Sabdo; Dhuyufurrahman, Ghifary; Aprianto, Adi (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
The family has an important position in Islam as the first and main place of education in the growth and development of a Muslim. Maintaining the integrity of the family is highly recommended in Islam. One of the factors that triggers the breakdown of family resilience is the difficulty of meeting economic needs which leads to shortcuts by gambling online and online loans with usury. Islam offers various solutions such as zakat, sadaqah and cash waqf. This research seeks to answer how the role of cash waqf in strengthening the resilience of Muslim families. This research uses a qualitative method with a type of library research. Primary data sources are Islamic jurists’ opinions, MUI fatwas and statutory regulations; secondary data are books, journals, documents and related research. Data collection uses data documentation and analysis by collecting, reducing, presenting, and concluding the results. The results of the research show that cash waqf can play a role in strengthening Muslim families with the qardhul hasan method, nazir cooperation with Muslim families in cash waqf, and investment of cash waqf to distribute its profits to Muslim families.